DEPICTING THE MOROCCAN MUSLIM WOMAN'S STRUGGLE AGAINST THE PATRIARCHAL AFRICAN-MUSLIM CONTEXT IN THE POSTCOLONIAL MOROCCO - El Aissi, Hanane; Muflichah, Siti (UIN Antasari Banjarmasin, 2023)
This essay aims to show how much Leila Abouzeid, the author of the novel Year of Elephant, has developed her own discursive space in order to express the unspoken and depict the abrupt trauma of postcolonial Morocco from a postcolonial feminist perspective. The concept of